(untitled) (JOURNAL OF ADVANCES IN CHEMISTRY, 2015)
The article presents the results of studies on the metal-based composites on the basis of copolymers and block copolymers of styrene with butoxymethyl methacrylate (BOMMA) as a catalyst in the oxidation process of naphthene paraffin fraction, which was obtained by extraction method ofÂ dearomatization of diesel fraction. It was shown that at low concentrations of metals of variable valency in the content of the catalyst here is sufficiently high yield of synthetic petroleum acids.